Optimizing Intermediary Functions in Alignment with Zakat Core Principles: Enhancing Baznas Merangin - Kholik, Abdul; Martiandi, Tommy; Setyagustina, Kurniasih; Din, Zia Ud; Malik, Agni Muhammad (Talaa : Journal of Islamic Finance, 2023)
This research is prompted by the issue of the potential of zakat (charitable donations) in Merangin in 2022, amounting to 183.33 billion, while the income of Baznas Merangin in 2022 was 9 billion. The study assesses the level of implementation of ZCP (Basic Zakat Principles), particularly the intermediary function aspect of Baznas. It then identifies the reasons why Baznas (National Amil Zakat Agency)  is unable to optimize its potential. This research is a field study and falls under the qualitative research category. The findings indicate that the intermediary function performed by Baznas Merangin in the management of zakat collection is very effective, with an increasing level of public trust in Baznas Merangin's performance in zakat management. The research is beneficial for Baznas Merangin. It is advisable to also focus on efforts to remind the public to fulfill zakat through official Zakat Management Institutions, such as being more active on social media platforms currently popular among the public, so that people become acquainted with Baznas as an official and potential Zakat institution. Institutional goals are anticipated to be achieved.